Nematodes of the nine-banded armadillo, Dasypus novemcinctus (Xenarthra: Dasypodidae) in Rio Grande do Sul, Brazil - Gomes, Sâmara Nunes; Pesenti, Tatiana Cheuiche; Aguiar, Cintia Lidiane Guidotti; Müller, Gertrud (Zootaxa, 2011)
Dasypus novemcinctus, Linnaeus, 1758 (Dasypodidae) occurs from Southern United States to South America (Reis et al. 2006). They have fossorial terrestrial habits, and the majority of the species construct burrow and excavate the soil to obtain food (Carter & Encarnação 1983). They are essentially solitary except during the brief mating period. Many armadillos of this species are run over and killed on highways (Fischer 1997) and they are also extensively hunted, but they are not listed as endangered due to their large distribution.